Twitter: A Digital Socioscope - Mejova, Yelena; Weber, Ingmar; Macy, Michael W. (Cambridge : Cambridge University Press, 2015)
How can Twitter data be used to study individual-level human behavior and social interaction on a global scale? This book introduces readers to the methods, opportunities, and challenges of using Twitter data to analyze phenomena ranging from the number of people infected by the flu, to national elections, to tomorrow's stock prices. Each chapter, written by leading domain experts in clear and accessible language, takes the reader to the forefront of the newly emerging field of computational social science. An introductory chapter on Twitter data analysis provides an overview of key tools and skills, and gives pointers on how to get started, while the case studies demonstrate shortcomings, limitations, and pitfalls of Twitter data as well as its advantages. The book will be an excellent resource for social science students and researchers wanting to explore the use of online data.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Twitter; Dyadic data analysis (Social sciences); Webometrics